Aberrant Expression of EZH2 in Pediatric Patients with Myelodysplastic Syndrome: A Potential Biomarker of Leukemic Evolution. (10th December 2019) - de Souza Fernandez, Teresa; Fonseca Alvarenga, Tatiana; Almeida Antônio de Kós, Elaiza; Lamim Lovatel, Viviane; Tavares, Rita de Cássia; da Costa, Elaine Sobral; de Souza Fernandez, Cecília; Abdelhay, Eliana
Abstract : Pediatric myelodysplastic syndrome (MDS) is an uncommon disease and little is known about the molecular alterations of its development and evolution to acute myeloid leukemia (AML). The Enhancer of Zeste Homolog 2 ( EZH2 ) is the catalytic subunit of Polycomb repressive complex 2 (PCR2). It is a histone methyltransferase, that targets lysine 27 of histone 3. This methylated H3–K27 is usually associated with the silencing of genes that are involved in fundamental cellular processes, such as cell proliferation and differentiation. There are only few studies showing the status of EZH2 expression in patients with MDS and they were performed in adult MDS patients. The aim of this study was to analyze the EZH2 expression in pediatric patients with MDS and its association with karyotypes and evolution to acute myeloid leukemia (AML). We conducted the first study of EZH2 expression in pediatric patients with MDS. Considering the EZH2 expression levels in 42 patients and 17 healthy pediatric donors, it was possible to define three groups of expression in patients: low, intermediate, and high. The intermediate level encompassed patients with normal karyotypes, low level included patients with monosomy 7 and del(7q) and high level included patients with trisomy 8 and del(11q) (p < 0.0001 ). Comparing the leukemic evolution, the low expression group presented disease evolution in 100% (8/8) of the cases, the intermediate expression group showed disease evolution in 4.34% (1/23) and in the high expression group, 63.63% (7/11) patients showed evolution from MDS to AML (p < 0.0001 ). It is important to note that low and high EZH2 expression are associated with leukemic evolution, however low expression showed a stronger association with evolution from MDS to AML than the high expression. Our results suggest a scale of measure for EZH2 expression in pediatric MDS, where aberrant EZH2 expression may be a potential biomarker of disease evolution.